A Succinct review of strengths, weaknesses, opportunities, and threats (SWOT) analyses, challenges and prospects of solar and wind tree technologies for hybrid power generation - Kumaresen, Mohanaravi; Samykano, Mahendran; Pandey, Adarsh Kumar; Noor, M. M.; K., Kadirgama (Frontiers Media S.A., 2024)
Introduction: The increasing global demand for sustainable energy solutions highlights the urgency of exploring renewable resources, particularly sunlight, which is abundant and virtually limitless. This study reviews innovative technologies like solar trees, wind trees, and hybrid solar-wind trees, which are emerging as efficient structures for harnessing renewable energy. Methods: A comprehensive SWOT analysis was conducted to evaluate the strengths, weaknesses, opportunities, and threats associated with solar, wind, and hybrid trees. The analysis also considered sustainability aspects, focusing on the efficiency and practicality of these technologies in various settings. Results: Solar trees mimic natural foliage, utilizing solar modules to convert sunlight into electricity, while wind trees incorporate micro-wind turbines and solar panels, effectively harnessing both wind and solar energy. Hybrid solar-wind trees combine these technologies to provide a consistent energy supply. These structures are compact, cost-effective, and adaptable to urban landscapes. Discussion: Challenges such as land use, aesthetic considerations, and public perception were identified. The review emphasizes the need for future research to optimize configurations and address these challenges, ensuring the successful integration of these technologies into sustainable urban landscapes. Conclusion: This review provides critical insights for renewable energy researchers, particularly in the development of hybrid wind and solar power systems, promoting energy security and climate resilience.